DNA damage induced by nitric oxide during ionizing radiation is enhanced at replication. - Folkes, L; O'Neill, P (2013)
Nitric oxide (NO) is a very effective radiosensitizer of hypoxic mammalian cells, at least as efficient as oxygen in enhancing cell death in vitro. NO may induce cell death through the formation of base lesions which are difficult to repair, and if they occur within complex clustered damage common to ionizing radiation, they may lead to replication-induced DNA strand breaks. It has previously been shown that 8-azaguanine and xanthine result from the reaction of guanine radicals with nitric oxide. We have now shown that adenine radicals also react with NO to form hypoxanthine and 8-azaadenine. Cells irradiated in exponential growth in the presence of NO are twice as radiosensitive compared to those irradiated in anoxia alone, whereas confluent cells are less radiosensitive to (•)NO. In addition, the numbers of DNA double strand breaks observed as γH2AX staining following radiosensitization by NO, are higher in exponential cells than in confluent cells. DNA damage, detected as 53BP1 foci, is also higher in HF-19 cells expressing Cyclin A, a marker for cells in S and G2 phases of the cell cycle, following radiosensitization by NO. RAD51 foci are highest in V79-4 cells irradiated in the presence of NO compared to in anoxia, 24h after radiolysis. This work presents evidence that radiosensitization of cells by NO is in part through the formation of specific DNA damage, difficult to repair, which in dividing cells may induce the formation of stalled replication forks and as a consequence replication-induced DNA strand breaks which may lead to cell death.